Surface structured bonded composite-metal joint - Di Giandomenico, Vincenzo (Cranfield University, 2014)
The design of structural joints is one of the critical challenges for the development of composite lightweight aircraft and motorsport structures. Despite the universal reliance upon mechanical fastening and adhesive bonding, the disadvantages of both when applied to high stiffness composites are considerable. For bolting and riveting these include added weight as laminates are thickened to account for stress concentrations. For bonding these include chemical uncertainties of the bonding process, inability to inspect for adhesive application quality and vulnerability to catastrophic failure. These concerns stimulated the drive for the development of new hybrid metal/composite joints which combine onlythe advantages of adhesive bonding and of mechanical interlocking by means of the pin-locking concept. This research project investigated the performance of several hybrid joint configurations obtained with the permutations of two different plate designs (double-scarf and double-stepped) and two surface feature shapes (spike and “shark teeth” pins). Tensile mechanical performance testing using the Digital Image Correlation (DIC) technique was carried on to examine the influence of the metal fitting geometry on the joint performance and strain distribution. The pins were manufactured using the processes of micro-machining (MM) and electron beam melting (EBM). The experimental results show a progressive pin failure advancing from the end of the overlap. Both surface features provide an increase in mechanical performance of the joint. Pin geometry such as the diameter, base width, length and shape critically affect the strength of the joint. The highest values of tensile strength are obtained with shark teeth pins which cause a severe reduction in stress concentration at the joint overlap edges and provide a more even strain distribution across the joining area increasing the joint strength. The plate design affects the strain distribution at high loads and can be modified so as to reduce the peel stress. The manufacturing process (EBM or MM) does not affect joint strength significantly (for spike pins) and the process choice can be made on economic grounds. The results provide a strong basis for more detailed stepped lap joint optimisation using tailored surface features designs to assist with the provision of robust, safe, very high strength and weight optimised joints.
Keywords: Metal fittings; surface features; embedded; hybrid metal/composite joint; digital image correlation; electron beam melting; micro-machining; pins